PERSEPSI MASYARAKAT TERHADAP PERILAKU MENYIMPANG (JUDI LIVE DINGDONG) DI DUSUN TANJUNG DESA SAWAH - Rezy, M. Ayyubi; Kadarisman, Yoskar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Live ding dong gambling is a type of gambling that is being developed in the community. Live ding dong gambling is one example of many social deviations that have an impact on society. Live ding dong gambling is played using internet access, in playing live ding dong gambling uses a dice ball that is played randomly and the dice number that comes out is the winner. Social deviation of live ding dong gambling in the past 2 years has developed very rapidly so that some people (actors) are active in participating in this social deviation activity. The existence of live ding dong gambling is responded by the public and the community carries out social control with the presence of live ding dong gambling activities and the impact of live ding dong gambling. The theory used in this research is the theory of perception and social control theory. This research is a descriptive quantitative research. The population in this study were all the people of Dusun Tanjung Desa Sawah. Data collection was carried out by observation, interviews after preparing a list of questions or questionnaires, and documentation. The results of this research can be concluded that the perception of the people of Dusun Tanjung Desa Sawah towards deviant behavior of live ding dong gambling is a negative perception. Meanwhile, in controlling / social control carried out by the people of Tannung Hamlet, Sawah Village, there is a weak control from the community. Keywords : Perception, Deviant Behavior (Live Ding Dong Gambling)